Utah Tuning Project - Randall S. Davies; David Williams (Universidad de Deusto, 2015)
Tuning is a faculty-driven initiative designed to improve the quality of higher education by establishing transparent and fully assessable learning outcomes and proficiencies for degrees, discipline by discipline. Unlike many other initiatives in the United States which function within an individual institution, the Utah Tuning Project involved all institutes of higher education within the state of Utah. The purpose of this paper is to document the findings from an evaluation of a multiyear project targeting four undergraduate degree programs involved in a tuning initiative. A summary of recommendations and best practices is provided, along with the challenges and benefits to individuals and programs engaged in this process.